Crystal structure, NMR and theoretical investigations on 2-(o-hydroxy-anilino)-1,4-napthoquinone - Feizi, Nourollah; Pinjari, Rahul V.; Gejji, Shridhar P.; Sayyed, Fareed B.; Gonnade, Rajesh G.; Rane, Sandhya Y. (Journal of Molecular Structure, 2010)
Crystal structure, (1)H NMR and cyclic voltammetric investigations of 2-(o-hydroxy-anilino)-1,4-napthoquinone (HAN), resulting from coupling of aminophenol with 2-hydroxy-1,4-napthoquinone, have been carried out. X-ray structure reveals that the HAN ligand crystallizes in orthorhombic space group Pca2(1) with Z = 4. forming a chain via inter-molecular O2 center dot center dot center dot H1A-O1 and C15-H15 center dot center dot center dot O3 interactions. Both (1)H NMR and cyclic voltammetry experiments suggest the titled ligand is associated and exists as dinner in d(6)-DMSO while the monomer has been predicted in CDCl(3) solution. Density functional calculations can be utilized to gauge the strength of hydrogen-bonded interactions from the (1)H chemical shifts in the NMR spectra. Self-consistent reaction field (SCRF) calculations further support the inferences drawn from cyclic voltammetry experiments. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: (1)H NMR; cyclic voltammetry; Density functional; hydrogen bonding; Napthoquinone

First naphthosemiquinone complex of K+ with vitamin K3 analog: experiment and density functional theory - Kathawate, Laxmi; Gejji, Shridhar P.; Yeole, Sachin D.; Verma, Prakash L.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2015)
Synthesis and characterization of potassium complex of 2-hydroxy-3-methyl-1,4-naphthoquinone (phthiocol), the vitamin K3 analog, has been carried out using FT-IR, UV-Vis, H-1 and C-13 NMR, EPR, cyclic voltammetry and single crystal X-ray diffraction experiments combined with the density functional theory. It has been observed that naphthosemiquinone binds to two K+ ions extending the polymeric chain through bridging oxygens O(2) and O(3). The crystal network possesses hydrogen bonding interactions from coordinated water molecules showing water channels along the c-axis. C-13 NMR spectra revealed that the complexation of phthiocol with potassium ion engenders deshielding of C(2) signals, which appear at delta = similar to 14.6 ppm whereas those of C(3) exhibit up-field signals near delta similar to 6.9 ppm. These inferences are supported by the M06-2x based density functional theory. Electrochemical experiments further suggest that reduction of naphthosemiquinone results in only a cathodic peak from catechol. A triplet state arising from interactions between neighboring phthiocol anion lead to a half field signal at g = 4.1 in the polycrystalline X-band EPR spectra at 133 K. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: C-13 NMR; DFT; hydrogen bonding; Naphthosemiquinone; Phthiocol; Vitamin K3